2010
DOI: 10.1099/jmm.0.015818-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic detection and molecular epidemiology of extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae in a regional hospital in central Taiwan

Abstract: This study was conducted to detect the genes encoding extended-spectrum b-lactamases (ESBLs) and determine the epidemiological relatedness of 69 Escherichia coli and 33 Klebsiella pneumoniae isolates collected from a regional hospital in central Taiwan, mostly from inpatients (E. coli 87.0 %; K. pneumoniae 88.0 %). The phenotypes of these isolates were examined according to the combination disc method recommended by the Clinical and Laboratory Standards Institute. Most of the ESBL-producing E. coli and K. pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
2
29
2
1
Order By: Relevance
“…Plasmid CTX-M, TEM, and SHV extended-spectrum beta-lactamase gene frequency was higher in this study than in other literature sources, namely: 1) in this study plasmid CTX-M was 97.06% compared to 73.8 -85.4% elsewhere; 2) plasmid TEM was 71.32% compared to elsewhere 42.4 -62.3%; and 3) plasmid SHV was 63.97% compared to the wide range of 7.7 -62.3% in the literature (Hayakawa et al, 2013;Lin, Hsu, Chen, Huang, & Lo, 2010;Manoharan, Premalatha, Chatterjee, & Mathai, 2011). In addition, plasmid gene combination frequency was higher, compared to other similar studies: CTX-M+ TEM+ SHV+ plasmid gene combination (45.59% vs 25.64%); and CTX-M+ TEM+ SHVplasmid gene combination (68.38% vs 26.5-35.5%; Hayakawa et al, 2013;Manoharan et al, 2011).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Plasmid CTX-M, TEM, and SHV extended-spectrum beta-lactamase gene frequency was higher in this study than in other literature sources, namely: 1) in this study plasmid CTX-M was 97.06% compared to 73.8 -85.4% elsewhere; 2) plasmid TEM was 71.32% compared to elsewhere 42.4 -62.3%; and 3) plasmid SHV was 63.97% compared to the wide range of 7.7 -62.3% in the literature (Hayakawa et al, 2013;Lin, Hsu, Chen, Huang, & Lo, 2010;Manoharan, Premalatha, Chatterjee, & Mathai, 2011). In addition, plasmid gene combination frequency was higher, compared to other similar studies: CTX-M+ TEM+ SHV+ plasmid gene combination (45.59% vs 25.64%); and CTX-M+ TEM+ SHVplasmid gene combination (68.38% vs 26.5-35.5%; Hayakawa et al, 2013;Manoharan et al, 2011).…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies have demonstrated higher plasmid SHV gene frequency in the K. pneumoniae group, compared to the E. coli group (Manoharan et al, 2011), as well as slightly higher plasmid CTX-M gene frequency in the E. coli group and slightly higher plasmid TEM gene frequency in the K. pneumoniae group (Kargar et al, 2014;Lin, Hsu, Chen, Huang, & Lo, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The TEM enzyme was named after the patient from whom it was isolated, Temoneira, and was fi rst discovered in Escherichia coli in Greece. In addition, chromosomal-related CTX-Mtype ESBL was reported in Kluyvera ascorbata (11) . Detection of ESBL production is important, because ESBL-positive strains are associated with increased mortality as compared to ESBL-negative strains.…”
Section: Introductionmentioning
confidence: 99%
“…This was 50% in our research. In Taiwan, Chinfulin et al (2010) reported the prevalence of TEM gene in 69 E.coli isolates [24]. Shazi shaki et al (2010) reported that TEM is the most common resistance gene in E.coli of Neonatal Intensive Care Units (NICU) of Indian hospitals [2]).…”
Section: Discussionmentioning
confidence: 99%